2009
DOI: 10.1091/mbc.e08-10-1029
|View full text |Cite
|
Sign up to set email alerts
|

The Rho-Guanine Nucleotide Exchange Factor Domain of Obscurin Activates RhoA Signaling in Skeletal Muscle

Abstract: Obscurin is a large (ϳ800-kDa), modular protein of striated muscle that concentrates around the M-bands and Z-disks of each sarcomere, where it is well positioned to sense contractile activity. Obscurin contains several signaling domains, including a rho-guanine nucleotide exchange factor (rhoGEF) domain and tandem pleckstrin homology domain, consistent with a role in rho signaling in muscle. We investigated the ability of obscurin's rhoGEF domain to interact with and activate small GTPases. Using a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 100 publications
(159 reference statements)
2
54
2
Order By: Relevance
“…Moreover, it has been previously shown that ectopic expression of the obscurin RhoGEF motif in COS-7 cells or mouse tibialis anterior muscle results in increased GTP-bound RhoA [36]. Therefore, we hypothesized that in MCF10A breast epithelial cells, knockdown of giant obscurins would result in decreased RhoA activity and a concomitant reduction of RhoA-driven processes downstream of the Rho Activated Kinase (ROCK).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, it has been previously shown that ectopic expression of the obscurin RhoGEF motif in COS-7 cells or mouse tibialis anterior muscle results in increased GTP-bound RhoA [36]. Therefore, we hypothesized that in MCF10A breast epithelial cells, knockdown of giant obscurins would result in decreased RhoA activity and a concomitant reduction of RhoA-driven processes downstream of the Rho Activated Kinase (ROCK).…”
Section: Resultsmentioning
confidence: 98%
“…The BCH domain in the C-terminal region of PRUNE2 has been reported to inhibit RhoA and cellular transformation mediated by Lbc RhoGEF (Soh and Low 2008). On the other hand, OBSCN protein was reported to possess RhoGEF activity and to activate RhoA (Bowman et al 2008;Ford-Speelman et al 2009). It is possible that PRUNE2 and OBSCN may competitively regulate RhoA activity, thus contributing to the characteristics of LMS and GIST cells.…”
Section: Discussionmentioning
confidence: 99%
“…The RhoGEF domain of obscurin interacts and colocalizes with RhoA, a small GTPase, at the M-band (FordSpeelman et al 2009). Exogenous expression of the obscurin RhoGEF domain in adult skeletal muscle activates RhoA, resulting in increased GTP-bound RhoA and a partial redistribution of RhoA to the cytoplasm, the I-band, and the Z-disc (Ford-Speelman et al 2009). A downstream target of RhoA, Rho associated coiled-coil containing kinase 1 (ROCK1), which functions in a variety of cellular activities, including actin cytoskeletal organization, cell adhesion, and proliferation, also exhibited increased activation in the same system (FordSpeelman et al 2009).…”
Section: Obscurins Function As Signaling Mediators At M-bandsmentioning
confidence: 99%
“…In addition, giant obscurins expressing the RhoGEF epitope are significantly increased in murine models of aortic constriction (Borisov et al 2003), and increased RhoA and ROCK1 activity have been observed in murine models of cardiac hypertrophy (Ford-Speelman et al 2009). Taken together, these findings support a role of the obscurin RhoGEF domain in regulating RhoA activity and suggest possible signaling functions for obscurins in the response to myocyte injury.…”
Section: Obscurins Function As Signaling Mediators At M-bandsmentioning
confidence: 99%